Tinjauan Literatur tentang Penerapan Kurikulum Merdeka di Tingkat Sekolah Menengah Atas (SMA): Penelitian - Salsabila Muharani; S. Syamsurizal (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the implementation of the Merdeka Curriculum at the senior high school level through a literature review. The study was conducted using a systematic review approach, which was structured based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. Data sources were obtained from five main articles that discussed various implementation strategies, challenges, and forms of implementation of the Merdeka Curriculum in several senior high schools. The findings of the study indicate that the Merdeka Curriculum is designed to be more adaptive, enjoyable, and aligned with the characteristics and developmental stages of students. Teachers have the freedom to design Learning Objective Pathways (ATP), use teaching materials relevant to the context, and apply learning that adapts to the individual needs of students. The Problem-Based Learning (PBL) and Project-Based Learning (PjBL) models are the main approaches that encourage active student participation and character development. However, the implementation of this curriculum still faces challenges such as limited teacher understanding, infrastructure constraints, and regional disparities.